2010
DOI: 10.1155/2010/803815
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Toxicity Induces Ras Signaling in Human Neuroblastoma SH-SY5Y Cultured Cells

Abstract: It has been reported that overproduction of reactive oxygen species occurs after brain injury and mediates neuronal cells degeneration. In the present study, we examined the role of Ras signaling on hydrogen peroxide-induced neuronal cells degeneration in dopaminergic neuroblastoma SH-SY5Y cells. Hydrogen peroxide significantly reduced cell viability in SH-SY5Y cultured cells. An inhibitor of the enzyme that catalyzes the farnesylation of Ras proteins, FTI-277, and a competitive inhibitor of GTP-binding protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
(17 reference statements)
3
5
0
Order By: Relevance
“…Our data clearly demonstrate that H 2 O 2 induced a great cell viability lost (by about 40%), in agreement with Chetsawang et al [ 31 ] who found SH-SY5Y cells loss viability mediated by H 2 O 2 . Those authors suggest that Ras protein could be involved in this cell survival decrease.…”
Section: Discussionsupporting
confidence: 93%
“…Our data clearly demonstrate that H 2 O 2 induced a great cell viability lost (by about 40%), in agreement with Chetsawang et al [ 31 ] who found SH-SY5Y cells loss viability mediated by H 2 O 2 . Those authors suggest that Ras protein could be involved in this cell survival decrease.…”
Section: Discussionsupporting
confidence: 93%
“…Treatment of ALA in concentration of 1–25 µg/mL to SH-SY5Y cells did not affect cellular conditions in our preliminary study, thus we decided to assess the neuroprotective effect of ALA at a concentration range of 1–25 µg/mL. In agreement with previous studies [ 36 37 ], we observed that SH-SY5Y cells exposed to H 2 O 2 treatment resulted in cell loss. However, treatment with PO and ALA prevented the cell death, as confirmed by the cell viability assay.…”
Section: Discussionsupporting
confidence: 82%
“…The supernatant was then aspirated off and the formazan crystals were dissolved in 50 μL of DMSO. After 15 min of reaction time, the absorbance was measured at 570 nm using the Omega Star micro plate reader [66]. The experiments were performed in triplicate and the cells viability was expressed as percentages of survival relative to the control sample.…”
Section: Methodsmentioning
confidence: 99%